1990
DOI: 10.1172/jci114790
|View full text |Cite
|
Sign up to set email alerts
|

Congenital hypothyroidism, as studied in rats. Crucial role of maternal thyroxine but not of 3,5,3'-triiodothyronine in the protection of the fetal brain.

Abstract: To study the protective effects of maternal thyroxine (T4) and 3,5,3'-triiodothyronine (T3) in congenital hypothyroidism, we gave pregnant rats methimazole (MMI), an antithyroid drug that crosses the placenta, and infused them with three different doses of T4 or T3. The concentrations of both T4 and T3 were determined in maternal and fetal plasma and tissues (obtained near term) by specific RIAs. Several thyroid hormone-dependent biological end-points were also measured. MMI treatment resulted in marked fetal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
143
1
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 296 publications
(159 citation statements)
references
References 46 publications
12
143
1
2
Order By: Relevance
“…Mimicking intrauterine conditions by transient postnatal treatment with T 4 might improve some of the thyroidrelated events, such as maturation of thyroidal T 4 and T 3 synthesis. Van den Hove et al (personal communication) observed that treatment of the very premature (24 -32 weeks GA) PT neonates for 3 days or more with 10 g T 4 /kg BW⅐day resulted in increases in the degree of iodination of Tg and the proportion of I found as T 4 and T 3 , to values similar to those in T neonates.…”
Section: Consequences Of the Proposed Interpretation Of The Present Rmentioning
confidence: 97%
See 2 more Smart Citations
“…Mimicking intrauterine conditions by transient postnatal treatment with T 4 might improve some of the thyroidrelated events, such as maturation of thyroidal T 4 and T 3 synthesis. Van den Hove et al (personal communication) observed that treatment of the very premature (24 -32 weeks GA) PT neonates for 3 days or more with 10 g T 4 /kg BW⅐day resulted in increases in the degree of iodination of Tg and the proportion of I found as T 4 and T 3 , to values similar to those in T neonates.…”
Section: Consequences Of the Proposed Interpretation Of The Present Rmentioning
confidence: 97%
“…Although the capacity to synthesize thyroglobulin (Tg), to concentrate iodine (I), and to synthesize T 4 and T 3 may start earlier, secretion of iodinated hormones by the fetal thyroidal is believed to start at midgestation, when hypothalamic-pituitary circulation matures, and TSH is secreted into the fetal blood (4,5). As shown in fetal serum obtained in utero by cordocentesis (6,7), T 4 and free T 4 (FT 4 ) do not clearly increase until 20 -24 weeks gestation, and free T 3 (FT 3 ) is mostly undetectable until after 32 weeks. Thus, the earlier in pregnancy, the more immature the fetal gland and the more important the proportion of fetal requirements that are met by the maternal contribution of hormone.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…MMI crosses the placenta and has been shown to inhibit fetal thyroidal function and promote severe fetal hypothyroidism with elevated serum TSH and low thyroid hormone levels in blood and tissues. Mothers are treated with thyroid hormone (T 4 , T 3 , or both) and, at any time during pregnancy or immediately after delivery, fetuses are dissected and blood/ tissues obtained for extraction and determination of T 4 and T 3 contents (345,346). Administration of tracer [ 125 I]T 4 to pregnant dams and its detection in fetal tissues has also been used to study placental transfer of thyroid hormone (347).…”
Section: And Recommendation 33mentioning
confidence: 99%
“…Pregnant rats were divided into two groups (n=30 in each group). Hypothyroidism was induced in rats using protocols described previously (Calvo et al 1990). Briefly, pregnant dams were given 0·025% 2-mercapto-1-methylimidazole (MMZ) in drinking water ad libitum from gestational day 8.…”
Section: Experimental Animalsmentioning
confidence: 99%